Influence of human peripheral blood samples preprocessing on the quality of Hi-C libraries - M. M. Gridina; E. Vesna; M. E. Minzhenkova; N. V. Shilova; O. P. Ryzhkova; L. P. Nazarenko; E. O. Belyaeva; I. N. Lebedev; V. S. Fishman (Вавиловский журнал генетики и селекции, 2023)
The genome-wide variant of the chromatin conformation capture technique (Hi-C) is a powerful tool for revealing patterns of genome spatial organization, as well as for understanding the effects of their disturbance on disease development. In addition, Hi-C can be used to detect chromosomal rearrangements, including balanced translocations and inversions. The use of the Hi-C method for the detection of chromosomal rearrangements is becoming more widespread. Modern high-throughput methods of genome analysis can effectively reveal point mutations and unbalanced chromosomal rearrangements. However, their sensitivity for determining translocations and inversions remains rather low. The storage of whole blood samples can affect the amount and integrity of genomic DNA, and it can distort the results of subsequent analyses if the storage was not under proper conditions. The Hi-C method is extremely demanding on the input material. The necessary condition for successfully applying Hi-C and obtaining high-quality data is the preservation of the spatial chromatin organization within the nucleus. The purpose of this study was to determine the optimal storage conditions of blood samples for subsequent Hi-C analysis. We selected 10 different conditions for blood storage and sample processing. For each condition, we prepared and sequenced Hi-C libraries. The quality of the obtained data was compared. As a result of the work, we formulated the requirements for the storage and processing of samples to obtain high-quality Hi-C data. We have established the minimum volume of blood sufficient for conducting Hi-C analysis. In addition, we have identified the most suitable methods for isolation of peripheral blood mononuclear cells and their long-term storage. The main requirement we have formulated is not to freeze whole blood.